THE INFLUENCE OF WORK LIFE BALANCE AND SOCIAL SUPPORT ON BURN OUT IN GBKP PRIESTS - Josep Sianturi; Sri Milfayetty; Hasanuddin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
Burn Out currently has many problems in carrying out services or in work professions. Burn Out is certainly influenced by many factors. This research aims to analyze and determine the influence between Work Life Balance and social support and Burn Out. This research is included in causal associative quantitative research. The sample for this research was 91 pastors at GBKP spread across sub-districts in Kaban Jahe. Research data was collected using a research scale that was declared valid and reliable. The data analysis technique uses multiple linear regression analysis. The research results show that (1) There is a significant relationship between work life balance burnout. This can be seen in the model summary table where the correlation r is 0.836 and p = 0.000. The correlation is positive, meaning that if compensation is high then burnout will also increase. The determinant coefficient R² is 0.699, meaning that 69.9% of burnout is influenced by work life balance. Based on the results of this research, it can be stated that hypothesis 1 proposed is accepted. (2) There is a significant relationship between social support and burnout. This can be seen in the model summary table where the correlation r is 0.890 and p = 0.000. The correlation is positive, meaning that if social support increases, burnout will also increase. The determinant coefficient R² is 0.793, meaning that 79.3% of burnout is influenced by social support. Based on the results of this research, it can be stated that hypothesis 2 proposed is accepted. (3) Together, the variables work life balance and social support have a significant relationship with burnout. This can be seen from the model summary table where the correlation r is 0.895 and p = 0.000. This means that together variables X1 and X2 influence variable Y. Based on the results of this research, the three hypotheses proposed in this research are declared accepted. The determinant coefficient R² is 0.801, meaning that 80.1% of burnout is influenced by work life balance and social support. Meanwhile, 19.9% ​​is influenced by other factors that cannot be explained in the regression equation (residual). Thus it can be concluded that psychological well-being and social support jointly influence teacher performance, the contribution of both in improving teacher performance is 35.2% while the remaining 64.8% can be explained by other variables outside the variables proposed in the research.